Theoretical justification of the main parameters of the coulter group of the sod seeder for strip sowing - V. A. Sysuev; S. L. Demshin; D. A. Cheremisinov; M. S. Doronin (Аграрная наука Евро-Северо-Востока)
Increasing the efficiency of direct strip sowing of grass seeds by means of seeders with active furrow openers is possible when seed and fertilizer working bodies are removed from the zone of operation of disk milling cutters. A structural and technological scheme of the coulter group of the sod seeder for strip sowing is proposed, which consists of a milling furrow opener, fertilizer and seed coulters mounted on leashes in the form of torsion spring trailers, and a rolling roller. To ensure high quality multilevel sowing of grass seeds and granules of mineral fertilizers, it is necessary at the design stage to determine the length of the fertilizer coulter sides, which prevent premature shedding of soil from the furrow walls until the mineral fertilizer granules reach the bottom of the furrow, and the minimum allowable distance between the fertilizer and seed coulters, which allows to cover the granules of mineral fertilizers with soil completely while maintaining the compact design of the coulter group. In the course of theoretical research, mathematical dependences were obtained to determine the rational parameters and operating modes of the coulter group of the proposed design, which will ensure a minimum spread of mineral fertilizer granules over the depth of incorporation and a high stability of the soil layer thickness between mineral fertilizer granules and grass seeds. Rational parameters of the coulter group of the proposed design are determined for the range of operating speeds of the sod seeder for strip sowing: angle at the apex of the shank fertilizer coulter in the horizontal plane is 15-20º, the length of the fertilizer coulter sides is 0.040-0.045 m, the width of the fertilizer coulter bell is 0.02 m, minimum permissible distance between the fertilizer and seed coulters is 0.14-0.16 м.